Economic importance of the Hungarian sports sector in international comparison - Koroknay, Zsuzsa (Applied Studies in Agribusiness and Commerce, 2020)
Sport is one of the most dynamically developing sectors in the world. During my research, I was looking for the answer to why and how the economic aspects of sport have evolved in recent times. I examined and evaluated sports economy indicators for the global (The European Union) and territorial (Hungary) units (for the last twenty years). The need for measurability is constantly increasing nowadays. This can also be seen in the markets of the sports sector, so we can find databases that are increasingly expanding in this sector. I have analysed EUROSTAT databases - with indexing – which can provide relevant information. The research field was two economic aspects, the number of employee and trade in sporting goods. The number of employees was analysed separately by the European Union and Hungary. In the examination of trade in sporting goods The Hungarian trade in sporting goods was compared to the neighbouring European Union countries. Based on my results, I can say that the economic importance of the sports sector has increased within the European Union and Hungary as well because the number of employed people in sports and the trade in sporting goods has increased.JEL Code: L83, Z20ARTICLE IN PRESS!